2005
DOI: 10.1021/jp051967y
|View full text |Cite
|
Sign up to set email alerts
|

Melting Curve and High-Pressure Chemistry of Formic Acid to 8 GPa and 600 K

Abstract: We have determined the melting temperature of formic acid(HCOOH) to 8.5 GPa using infrared absorption spectroscopy, Raman spectroscopy and visual observation of samples in a resistively heated diamond-anvil cell. The experimentally determined melting curve compares favorably with a twophase thermodynamic model. Decomposition reactions were observed above the melting temperature up to a pressure of 6.5 GPa, where principal products were CO 2 , H 2 O and CO. At pressures above 6.5 GPa, decomposition led to solid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 27 publications
1
22
0
Order By: Relevance
“…The calculations estimate a shock temperature of ~600 K at 5.5 GPa, and ~2100 K for 23.0 GPa. Even using our calculated temperatures as a minimum value [11], these pressures and temperatures place the shocked formic acid states in the decomposition region of the static P-T phase diagram reported by Montgomery et al [5]. However, under our shock conditions, we do not observe any indication of the volume change expected with reaction.…”
Section: Resultsmentioning
confidence: 46%
See 1 more Smart Citation
“…The calculations estimate a shock temperature of ~600 K at 5.5 GPa, and ~2100 K for 23.0 GPa. Even using our calculated temperatures as a minimum value [11], these pressures and temperatures place the shocked formic acid states in the decomposition region of the static P-T phase diagram reported by Montgomery et al [5]. However, under our shock conditions, we do not observe any indication of the volume change expected with reaction.…”
Section: Resultsmentioning
confidence: 46%
“…Additionally, more recent molecular dynamics calculations and low temperature, static high-pressure diamond-anvil cell experiments indicate reaction may occur at roughly 16 -21 GPa at room temperature, as proposed in Equation 1 [3,4,5]. In order to investigate the shock wave response of this simple organic carboxylic acid, we have examined its behavior with embedded magnetic-gauge gas gundriven plate impact experiments at 5.5 -23.0 GPa.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, in this wavenumber range, palmitic and sebacic acid have prominent clusters of peaks in the 2800–3000 cm −1 region, which are due to the antisymmetric and symmetric stretching vibrations of methyl and methylene groups. Sebacic acid shows the rapid shift of the OH band to lower wavenumbers with pressure associated with pressure‐induced crystallization and the formation and symmetrization of long chains of intermolecular OH…O bonds in carboxylic acids . No such shift is present in palmitic acid, again suggesting that intermolecular hydrogen bonding in this material remains limited to dimer formation.…”
Section: Resultsmentioning
confidence: 97%
“…The vibrational features in the wavenumber region between 2500 and 3000 cm À1 are assigned to a BA dimer formed through intermolecular hydrogen bonding. [30][31][32] Figure 2 shows the temperature-dependent infrared spectra of neat BA. It was found that most vibrational modes of BA did not change significantly and the intensities became weaker as temperature was increased.…”
Section: Resultsmentioning
confidence: 99%